Berlin Excor Cannulation of Left Atrial Appendage in Left Ventricular Restrictive Physiology: A Novel Bailout Strategy. Issue 9 (18th December 2020) - Marey, Gamal M.; Said, Sameh M.; Ameduri, Rebecca; Steiner, Marie E.; Bowler, Michael; Loomis, Ashley; Jang, Subin; Griselli, Massimo
Abstract : Ventricular assist device (VAD) management continues to be a challenge in the presence of restrictive physiology. Left atrial (LA) decompression is not satisfactory even with good function and position of the left ventricular cannula. We describe an alternate approach with LA cannulation via the left atrial appendage (LAA) as a rescue strategy in a patient who had restrictive physiology, in our case was secondary to viral myocarditis acute systolic heart failure with subsequent insidious diffuse endomyocardial fibrosis and superimposed massive calcification, causing inadequate emptying of the left ventricle despite optimal VAD apical cannula position.